Motor activity of children with disabilities in conditions of mixed education as scientific and pedagogical problem - Kurivskyi, Y.; Iedynak, G. (Journal of Education, Health and Sport, 2023)
The key challenges of the educational process in the conditions of war are limited ways of organizing motor activity, reduced motivation to use various forms of such activity and deterioration of the psycho-emotional state of participants in the educational process. Goal of research is to identify pedagogical problems in ensuring the appropriate level of motor activity of children with disabilities in the context of mixed education. Research methods used: theoretical analysis, systematization, comparison of different views on the investigated problem, generalization of data from scientific and methodological and special literature. The results. It was found that motor activity is considered as a means of achieving the highest possible positive result in the specified indicators of the state of functioning of body systems. The leading place in this process is given to expanding the potential of PE in the process of getting an education. The main pedagogical problems that require a systematic and comprehensive solution in the process of inclusive physical education of children with disabilities, which is implemented in a mixed format, are highlighted: ensuring the implementation of the fundamentals of inclusive pedagogy; flexibility in planning and modification of activities aimed at ensuring the optimal level of motor activity of children with disabilities; a comprehensive approach to problem-solving; permanent monitoring and implementation of new domestic and foreign practices for the implementation of high-quality remote physical education, development of motivation in children with disabilities for systematic physical activity; ensuring independent motor activity of children with disabilities in conditions of mixed education; a differentiated approach in the implementation of motor activity; implementation of a multisensory strategy. Conclusions. The possibilities of mixed learning in the implementation of physical education for children with disabilities as a means of realizing the appropriate level of their motor activity have been clarified. The identified problematic aspects lead to the need to develop a new model of the inclusive physical education process for a system-wide solution. This approach is based on interdisciplinary integration processes of using distance technologies and innovative technologies of mixed learning to solve the issues.